2022
DOI: 10.1021/acs.jpcc.2c03881
|View full text |Cite
|
Sign up to set email alerts
|

Plasmonic Heating Effects in Tip-Enhanced Raman Spectroscopy (TERS)

Abstract: Tip-enhanced Raman spectroscopy (TERS) is a spectroscopy technique that possesses single-molecule sensitivity and subnanometer spatial resolution. These unique properties are achieved thanks to the extremely high electromagnetic field confinement at the apex of the scanning probe. However, such strong field confinement can lead to photodecomposition and thermal decomposition of the analytes. Here, we demonstrate that the use of an aqueous solvent as tip−sample junction mediator drastically reduces possible mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 44 publications
1
6
0
Order By: Relevance
“…As shown in detail by our previous work, the overall reaction kinetics were essentially modulated by the photoactivated O 2 – radicals at its steady state concentrations, which exhibited a linear dependence on P ex . The linear P ex -dependence of k obs also indicated that under this reaction condition, the pNTP coupling reaction was driven by plasmonic hot electrons without any significant influence by photothermal heating. ,, Because of the small excitation volume of the confocal illumination and high thermal conductivity of water, the heat produced through photothermal transduction was rapidly dissipated to the aqueous reaction environment, resulting in a rather insignificant elevation of the local temperatures on the photocatalyst surfaces. , In alkaline environments, 785 nm excitations gave rise to sublinear P ex -dependence of k obs for both pNTP and pNPA coupling reactions (lower panel of Figure D). Such sublinearity in power dependence is a common feature of semiconductor-driven photocatalytic reactions when the bulk electron–hole pair recombination becomes prevalent but has been rarely observed in plasmon-driven photocatalysis on metallic nanostructures .…”
Section: Resultsmentioning
confidence: 92%
“…As shown in detail by our previous work, the overall reaction kinetics were essentially modulated by the photoactivated O 2 – radicals at its steady state concentrations, which exhibited a linear dependence on P ex . The linear P ex -dependence of k obs also indicated that under this reaction condition, the pNTP coupling reaction was driven by plasmonic hot electrons without any significant influence by photothermal heating. ,, Because of the small excitation volume of the confocal illumination and high thermal conductivity of water, the heat produced through photothermal transduction was rapidly dissipated to the aqueous reaction environment, resulting in a rather insignificant elevation of the local temperatures on the photocatalyst surfaces. , In alkaline environments, 785 nm excitations gave rise to sublinear P ex -dependence of k obs for both pNTP and pNPA coupling reactions (lower panel of Figure D). Such sublinearity in power dependence is a common feature of semiconductor-driven photocatalytic reactions when the bulk electron–hole pair recombination becomes prevalent but has been rarely observed in plasmon-driven photocatalysis on metallic nanostructures .…”
Section: Resultsmentioning
confidence: 92%
“…21,27 Since the rate constant (K) equals the reciprocal of τ, 56 we can deduce the SM dissociation and association kinetics to the nanogap (K DIS ¼ 1=τ CAP and K ASS ¼ 1=τ REL , respectively 47,49,56 ) at the temperature at which the experiment was performed (RT). Despite the use of low and medium power (far-field) intensities, the photothermal effects (optical heating) [57][58][59] of exposure of the BDT molecule to laser illumination and the possible repercussions over its capture/release kinetics should be discussed here. As a very recent study revealed, 59 the expected local temperature increase is estimated to be below 3 K for the nearfield in a nanogap of Au-tip|Au-surface configurations in aqueous media using a tip radius of 25 nm, and under the same laser power densities here employed, even considering a field magnification of the order of 50, almost twice that of ours.…”
Section: Clustering and Statistics Of Capture And Release Statesmentioning
confidence: 99%
“…Despite the use of low and medium power (far-field) intensities, the photothermal effects (optical heating) [57][58][59] of exposure of the BDT molecule to laser illumination and the possible repercussions over its capture/release kinetics should be discussed here. As a very recent study revealed, 59 the expected local temperature increase is estimated to be below 3 K for the nearfield in a nanogap of Au-tip|Au-surface configurations in aqueous media using a tip radius of 25 nm, and under the same laser power densities here employed, even considering a field magnification of the order of 50, almost twice that of ours. This temperature increase is insufficient to promote Au-S desorption, 60 Au-Au fracture, 61 or thiol-Au bond instabilities that have been estimated to be significant from a temperature increase of 30 K. 62 Accordingly, the expected small (local) thermal increase will not affect the stability of the junction.…”
Section: Clustering and Statistics Of Capture And Release Statesmentioning
confidence: 99%
“…Indeed, engineered hybrid molecular-plasmonic nanostructures have enabled single molecule detection and identification via surface-enhanced Raman scattering (SERS). , The same effect is at the core of visualizing single molecules with subnanometer spatial resolution via tip-enhanced Raman scattering (TERS). More generally, modern applications of plasmon-enhanced spectroscopy and microscopy fueled advances in fields as diverse as quantum and semiconductor materials, heterogeneous catalysis, and the health sciences, to name a few. , All of these exciting developments and many more are addressed in this virtual special issue (VSI) on nanophotonics. From ultraprecise chemical imaging measurements performed in a scanning tunneling microscope chamber to single molecule spectroscopic measurements performed at solid–air and solid–liquid interfaces, , this VSI includes contributions from active practitioners that are all striving to better understand increasingly complex interfaces encountered in the biological, materials, and chemical sciences (see Figure ).…”
mentioning
confidence: 99%
“…6,7 All of these exciting developments and many more are addressed in this virtual special issue (VSI) on nanophotonics. From ultraprecise chemical imaging measurements performed in a scanning tunneling microscope chamber 3−5 to single molecule spectroscopic measurements performed at solid−air and solid−liquid interfaces, 8,9 this VSI includes contributions from active practitioners that are all striving to better understand increasingly complex interfaces encountered in the biological, materials, and chemical sciences (see Figure 1).…”
mentioning
confidence: 99%